Assessement of Candida albicans of the oral mucosa among type-2 diabetes mellitus patients attending Bahteramas Hospital, Southeast Sulawesi Province - Firdayanti Firdayanti; Angriani Fusvita; Ani Umar (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2025)
Diabetes Mellitus (DM) is a disease characterized by hyperglycemia resulting from either insulin deficiency or insulin resistance. Candida albicans is a fungus generally found on the surface of the mucous membrane, which usually dominates and overgrows among DM patients. This study aims to identify the presence of the C. albicans fungus on the oral mucosa of individuals with Type-2 Diabetes Mellitus at Bahteramas Hospital, Southeast Sulawesi Province, Indonesia. A descriptive study was employed, and a purposive sampling technique was used to select a sample of 62 patients. Swab samples were cultured on Potato Dextrose Agar medium for Gram staining and carbohydrate assimilation tests. The resulting culture was tested using CHROMagarTM Candida (CAC) media. Among the 62 samples, 56 samples were identified to have a convex colony, a cream-color surface, a smooth texture, and a Gram-positive nature. The carbohydrate assimilation test showed that the indicated samples could ferment glucose and maltose, but not lactose and sucrose. Green colonies are formed through CHROMagarTM Candida differential media testing. There are 56 identification results for C. albicans from oral mucosal swab samples from 62 patients with Type-2 Diabetes Mellitus at the Bahteramas Hospital, Southeast Sulawesi Province, yielding six other patients with negative results.